2019
DOI: 10.3906/bot-1804-23
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genomic instability and DNA methylation due to aluminum (Al) stress in wheat ( Triticum aestivum L.) using iPBS and CRED-iPBS analyses

Abstract: Aluminum (Al) toxicity is a serious factor restricting crop productivity in acid soil, and Al is the major cause of phytotoxicity. However, the role of Al toxicity in interprimer binding site (iPBS) polymorphism, genomic instability, and DNA methylation has not been fully investigated. In the current study, the effects of different Al concentrations on iPBS polymorphism, genomic instability, and DNA methylation were investigated in seedlings of three wheat cultivars: Haymana 79, Kılçıksız, and Bezostaja 1. A h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…In this respect, under salinity stress conditions the tomato plants exhibited significant changes in cytosine methylation status that can be referred to as hyper methylation. Likewise, several studies have demonstrated abiotic stresses, such as chromium nitrate, zinc, arsenic, and lead sulfate stress/toxicity in maize [17,43] and aluminum chlorite stress/toxicity in wheat [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, under salinity stress conditions the tomato plants exhibited significant changes in cytosine methylation status that can be referred to as hyper methylation. Likewise, several studies have demonstrated abiotic stresses, such as chromium nitrate, zinc, arsenic, and lead sulfate stress/toxicity in maize [17,43] and aluminum chlorite stress/toxicity in wheat [18].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Randomly Amplified Polymorphic DNA (RAPD) can be employed effectively to determine different toxicities in plants [14,15]. The coupled restriction enzyme digestion-random amplification (CRED-RA) method has been successfully used to assess cytosine methylation in the plant genome or toxicity caused by environmental stressors such as salinity [15,16], heavy metals [17,18], and pesticides [14,19,20]. Thus far, no reports exist that describe a protective effect of ZnO-NPs and PGPBs against salinity stress.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, metAFLP results demonstrated no differences in DNA methylation under stress conditions, suggesting that only a portion of the genome responds to Al stress. Pour et al (2019) used CRED_RA in three wheat cultivars (cv. Haymana79, Kılçıksız, and Bezostaja1) to evaluate genetic and epigenetic variations to different Al conditions (7.5 and 30mM).…”
Section: Epigenetic Mechanism Involved In Aluminum Toxicitymentioning
confidence: 99%
“…Therefore, these treatments increased the quality of lavender oil. Hosseinpour et al (2020) indicated that various molecular markers can detect genetic polymorphisms and diversity among plants individuals which are created by environmental stress such as salinity (Saleh, 2016), heavy metals (Hossein-Pour et al, 2019), pesticides (Taspinar et al, 2017) and nanoparticles (Hosseinpour et al 2020). Therefore, we used ISSR molecular markers to detected genetic diversity and polymorphism within and among the treated samples.…”
Section: Discussionmentioning
confidence: 99%